2013
DOI: 10.17705/1jais.00337
|View full text |Cite
|
Sign up to set email alerts
|

Information Technology, Materiality, and Organizational Change: A Professional Odyssey

Abstract: We begin with a retrospective reflection on the first author's research career, which in large part is devoted to research about the implications of information technology (IT) for organizational change. Although IT has long been associated with organizational change, our historical review of the treatment of technology in organization theory demonstrates how easily the material aspects of organizations can disappear into the backwaters of theory development. This is an unfortunate result since the material ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(38 citation statements)
references
References 65 publications
0
37
0
1
Order By: Relevance
“…Although the joint optimization of technical and social aspects was the hallmark of the sociotechnical systems approach, it tended at times to privilege the technical, or at other times the social (see Leonardi 2012;Orlikowski 2010). However, as Robey et al (2013) argue, privileging either is not inherent in the sociotechnical systems approach that remains capable of including the technical/material as well as the social/human in explaining organizational stability and change. Importantly, while doing so, the sociotechnical systems approach preserves the ontological distinctions between the social and the material, a position reinforced by more recent studies of IS and organizing that "demonstrate the viability of a socio-technical approach in which the ontological distinction between social and technical reality is maintained" (Robey et al 2013, p. 385; see also Leonardi 2011Leonardi , 2012.…”
Section: Sociotechnical Systemsmentioning
confidence: 99%
“…Although the joint optimization of technical and social aspects was the hallmark of the sociotechnical systems approach, it tended at times to privilege the technical, or at other times the social (see Leonardi 2012;Orlikowski 2010). However, as Robey et al (2013) argue, privileging either is not inherent in the sociotechnical systems approach that remains capable of including the technical/material as well as the social/human in explaining organizational stability and change. Importantly, while doing so, the sociotechnical systems approach preserves the ontological distinctions between the social and the material, a position reinforced by more recent studies of IS and organizing that "demonstrate the viability of a socio-technical approach in which the ontological distinction between social and technical reality is maintained" (Robey et al 2013, p. 385; see also Leonardi 2011Leonardi , 2012.…”
Section: Sociotechnical Systemsmentioning
confidence: 99%
“…Several scholars have suggested that examining affordances can inform studies of IT-associated organizational-change processes (Volkoff & Strong, 2013) and can help scholars develop theory on how technologies offer action possibilities to work teams and organizational units (Gaver, 1991;Robey, Anderson, & Raymond, 2013) and create new organizational forms (Leonardi, 2011;Zammuto et al, 2007). The focused nature of the affordance concept is especially useful in examining the effects of introducing technology to organizations in that it allows one to explain organizational-level affordances (Volkoff and Strong, 2013).…”
Section: Theoretical Lens: It Affordances and Actionsmentioning
confidence: 99%
“…One way to do so is to focus on a single affordance, which allows one to center on the way this focal affordance might unfold through time should an actor attempt to actualize it and on the other affordances or mechanisms that interact with the focal affordance. Lastly, one must conceptualize the affordances that material artifacts offer at a higher level of analysis than the individual level such that the analysis must scale up to describe the relationships between aggregated technologies and larger social collectives (Robey et al, 2013, Zammuto et al, 2007. This analysis is applicable to all major types of IT applications and to an organization as a whole.…”
Section: Theoretical Lens: It Affordances and Actionsmentioning
confidence: 99%
“…of IT-associated organisational change processes (Volkoff & Strong 2013), to theorise how technologies offer action possibilities to work teams and organisational units (Gaver 1991;Robey, Anderson & Raymond 2013) and to create new organisational forms (Leonardi 2011;Zammuto, Griffith, Majchrzak, Dougherty & Faraj 2007). The theory of affordance arose primarily from the field of ecological psychology (Gibson 1977).…”
Section: Selected Papers From Acis Ict-enabled Time-critical Clinicmentioning
confidence: 99%